2014
DOI: 10.1007/978-3-319-13734-6_18
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Content Selection in the Age of (Mis)Information

Abstract: Abstract. Despite the enthusiastic rhetoric about the so called collective intelligence, conspiracy theories -e.g. global warming induced by chemtrails or the link between vaccines and autism -find on the Web a natural medium for their dissemination. Users preferentially consume information according to their system of beliefs and the strife within users of opposite narratives may result in heated debates. In this work we provide a genuine example of information consumption from a sample of 1.2 million of Face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 33 publications
1
57
0
1
Order By: Relevance
“…Conspiracists tend to reduce the complexity of reality by explaining significant social or political events as secret plots conceived by powerful individuals or organizations. Misinformation can be particularly di cult to correct [2,3]. Recently [4] it has been shown that conspiracist and mainstream information reverberate in a similar way on social media and that users generally exposed to conspiracy stories are more prone to like and share satirical information [5].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Conspiracists tend to reduce the complexity of reality by explaining significant social or political events as secret plots conceived by powerful individuals or organizations. Misinformation can be particularly di cult to correct [2,3]. Recently [4] it has been shown that conspiracist and mainstream information reverberate in a similar way on social media and that users generally exposed to conspiracy stories are more prone to like and share satirical information [5].…”
Section: Introductionmentioning
confidence: 98%
“…The resulting dataset contains 73 public Facebook pages; 34 of such pages are related to scientific news and the other 39 to news that can be considered conspiratorial; we refer to the former as science pages and to the latter as conspiracy pages. Notice that the dataset used in the analysis is the same used in [3] and [5]. In Table 1 we summarize the details of our data collection.…”
Section: Introductionmentioning
confidence: 99%
“…The order parameters R 0 and R M allow us to quantify the impact of media nodes on content-spreading dynamics, where we note that one can also define timedependent analogs of (4) and (5). We define the media impact for one trial to be the ratio of the mean baseline ideological distance to the media-influenced ideological distance in that trial:…”
Section: B Media Influence With a One-dimensional Opinion Spacementioning
confidence: 99%
“…Individual user preferences play a strong role in the choice to consume news that conforms to (or even enhances) previously held views [4]. One reason that propaganda, misinformation, and disinformation has become so widespread on social media networks is that users are more likely to share a false or misleading story if it seems to confirm or support their biases [5,6]. Another challenge is that content is also spread and amplified through bot, cyborg, and sockpuppet accounts [7].…”
Section: Introductionmentioning
confidence: 99%
“…To enrich this original dataset, we use the Twitter REST API to obtain all tweets of users who have participated in the discussion at least once. 6 Admittedly, this dataset might su er from sampling bias, however the topics are speci c enough that the distortion should be negligible [28]. There might also be recency bias due to the addition of the latest tweets of the users.…”
Section: Datasetmentioning
confidence: 99%